PENGARUH SUKUK OUTSTANDING DAN PERINGKAT SUKUK TERHADAP PROFITABILITAS BANK - Acim, Acim; Taufik Hidayat, Rida; Yuliasari, Tia (Sekolah Tinggi Agama Islam Putra Galuh Ciamis, 2025)
This study examines the influence of Sukuk Outstanding and Sukuk Ratings on the Profitability of Islamic Banks listed on the Indonesia Stock Exchange. The urgency of this research is based on the phenomenon of fluctuations in Islamic bank profitability despite an increase in sukuk issuance, as well as differences in sukuk ratings that reflect the level of risk and credit quality of banks. This study uses a quantitative approach with descriptive and verification methods. Data analysis techniques include correlation coefficients, coefficients of determination, t-tests, multiple linear regressions, and F-tests. The results show that Sukuk Outstanding has a positive and significant effect on Islamic Bank Profitability, Sukuk Ratings have a positive and significant effect on Islamic Bank Profitability, and Sukuk Outstanding and Sukuk Ratings simultaneously have a significant effect on Islamic Bank Profitability. The implications of this research emphasize the importance of optimal sukuk management and improving the quality of sukuk ratings to support the performance and sustainability of Islamic banks